Pengaruh Kompetensi, Komitmen Organisasi Dan Digitalisasi Terhadap Kinerja Karyawan Divisi Airport Maintenance PT . Angkasa Pura II Bandara Internasional Kualanamu - Lasman Situmorang; R. Sabrina; Fajar Pasaribu (Journal of Business and Economics Research (JBE), 2023)
The purpose of this study was to determine the effect of competence, organizational commitment and digitization on the performance of employees of the Airport Maintenance Division of PT Angkasa Pura II Kualanamu International Airport Branch. This study uses a quantitative associative approach, which is an approach to determine the effect of independent variables and dependent variables where data is collected in quantitative form to examine certain populations or samples with the aim of testing predetermined hypotheses. The population in this study were employees of the Airport Maintenance Division of PT Angkasa Pura II Kualanamu International Airport Branch Office. The sample in this study used a sample of 57 people consisting of 15 employees of the Electronic Facility & IT Division, 23 employees of the Electrical & Mechanical Facility Division and 19 employees of the Infrastructure Division. Data collection techniques through questionnaires that have been tested for validity and reliability. The data analysis used is the Structural Equation Model (SEM) method with the Partial Least Square (PLS) method. The results of this study indicate that: (1) Competence has a positive and significant effect on the performance of employees of the Airport Maintenance Division of PT Angkasa Pura II Kualanamu International Airport Branch with a value of 0.293 and P-Values ​​= 0.033 <0.05. (2) Organizational commitment has a positive and significant effect on the performance of employees of the Airport Maintenance Division of PT Angkasa Pura II Kualanamu International Airport Branch with a value of 0.374, and P-Values ​​= 0.033 <0.05. (3) Digitization has a positive and significant effect on the performance of employees of the Airport Maintenance Division of PT Angkasa Pura II Kualanamu International Airport Branch Office with a value of 0.339 and P-Values ​​0.008 <0.05. (4) Competence, organizational commitment and digitization have a positive and significant impact on the performance of employees of the Airport Maintenance Division of PT Angkasa Pura II Kualanamu International Airport Branch.